1993
DOI: 10.1021/j100120a045
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cyano substitution on the heats of formation of organic ions and neutrals

Abstract: In this paper the effect of the cyano group (CN) on the heats of formation of small, gas-phase organic cations was investigated. The C N substituent has a predictable and significant influence on cationic heats of formation which does not vary greatly for saturated and unsaturated ions. It was found to increase the AfHo298 of radical cations by 42-44 kcal mol-' compared with their H-substituted analogues. The effect of C N substitution on neutral molecules is ca. 32 kcal mol-', and so the ionization energy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 2 publications
1
8
0
Order By: Relevance
“…The IP(a) values of intermediates IM2 and IM6, and the product HCCN cannot be obtained and are labeled by "-" in Table IV as well as SF 6 , which can be dissociated by electron attachment. 31 The results show that the theoretical values of IP(a) and EA(a) are in good agreement with the corresponding experimental values, 30 indicating that our theoretical results are reasonable and reliable. The IPs and EAs of molecules are very important parameters to estimate their abilities of reduction and oxidation, respectively.…”
Section: B Energies: Frontier Mos Ips and Eassupporting
confidence: 75%
“…The IP(a) values of intermediates IM2 and IM6, and the product HCCN cannot be obtained and are labeled by "-" in Table IV as well as SF 6 , which can be dissociated by electron attachment. 31 The results show that the theoretical values of IP(a) and EA(a) are in good agreement with the corresponding experimental values, 30 indicating that our theoretical results are reasonable and reliable. The IPs and EAs of molecules are very important parameters to estimate their abilities of reduction and oxidation, respectively.…”
Section: B Energies: Frontier Mos Ips and Eassupporting
confidence: 75%
“…It was evident that the cyano functionality had a predictable effect on the thermochemistry of several classes of radical cations, raising their heats of formation by 42-44 ± 3 kcal mol-1 relative to a hydrogen substituent. 1 The resulted indicated that the CN group acted predominantly as an inductive electron-withdrawing group and did not greatly participate in charge delocalization of the cationic center. The appearance energy (AE) technique3•4 was employed to determine new thermochemistry for the even electron cations +CH2CN, CH3+CHCN, and (CH3)2+CCN and to confirm the Af7f029s(*CH2CN) derived from gas phase kinetic studies.…”
Section: Introductionmentioning
confidence: 99%
“…The degree of -delocalization in the linear cations and radicals was estimated by using the above thermochemical data in isodesmic reactions 1 and 2. +CH2CN(NC) + CH4 + AE -*• CH3CN(NC) ++CH3 (1) *CH2CN(NC) + CH4 + AE -CH3CN(NC) + *CH3 (2) Alone, the values for the exothermicity (-ve AE) or endothermicity (+ve AE) are of limited use. To put them into perspective, the CN and NC substituents were compared to other groups using their respective forms of eqs 1 and 2.…”
mentioning
confidence: 99%
“…All five quartic centrifugal distortion constants, five of the seven sextic, and one octic could be determined with sufficient accuracy and yielded the best fits. Only for the 18 O-species we had to restrict the measurements from 18 to 26 GHz and to 13 a-type transitions with a standard deviation of 54 kHz. Besides the rotational constants only two quartic distortion constants could be fitted; the rest was fixed to the corresponding values of the parent molecule.…”
Section: Rotational Spectra and Spectroscopic Constantsmentioning
confidence: 99%
“…Extensive theoretical calculations about the structure, reactivity, and energetic quantities have been carried out [15][16][17]. Production of the molecule under high vacuum conditions by flash thermolysis of different precursors allowed the measurement of its heat of formation and an estimate of the ionization energy by mass spectroscopic techniques [18], the determination of the IR-bands in an Ar matrix at 12 K [19], and to find the pathways of its formation also by trapping the different species in an Ar matrix at 14 K [16]. The latter paper contradicts strongly a finding of Efremov et al [20] who claim that cyanoketene can be isolated as a liquid, boiling at )34°C, and who published an NMR spectrum.…”
Section: Introductionmentioning
confidence: 99%